E-LEARNING AND DIGITAL PEDAGOGY IN NIGERIAN UNIVERSITIES FOR STUDENTS’ LEARNING IN SOUTH-WESTERN NIGERIA - Dr Lucky Julius ILAVBARE; Bright Irene EWERE (International Journal of Educational Excellence and Innovation, 2025)
The purpose of this study is to investigate the process of digital pedagogy uptake, utilization, and efficacy at a selection of universities located in Southwestern Nigeria. A mixed-methods strategy was utilized to collect data from a total of 300 students and 100 instructors through the use of structured surveys. Finally, descriptive and inferential statistics were utilized to analyze the extracted information. According to the data, younger students between the ages of 18 and 25 are the most active users of e-learning platforms, whilst older professors (those aged 36 and older) are less engaged, most likely because of their lower level of digital competency. The utilization of digital learning technologies, like Learning Management Systems (LMS) and mobile learning apps, continues to be lower among professors than it is among students, despite the ubiquitous availability of these resources. With 85 percent of respondents believing that digital pedagogy enhances knowledge, engagement, and accessibility to resources, the findings suggest that digital pedagogy has a beneficial impact on the outcomes of learning.However, the full adoption of digital pedagogy is impeded by challenges such as inadequate infrastructure, limited technical support, and poor internet accessibility. The study, using a chi-square test, has shown a statistically significant correlation (p < 0.05) between digital pedagogy and learning outcomes. To fully harness the benefits of e-learning at Nigerian universities, the study underscores the need for urgent improvements in faculty training, infrastructure, and the implementation of policy interventions.